Website Quality, Tourist Experience, Satisfaction, And Loyalty At Badung Market - Anak Agung Made Dwi Putri Kusumayanti; I Putu Utama; Ni Made Eka Mahadewi (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study investigates the relationship between website quality, memorable tourism experience, tourist satisfaction, and loyalty in the context of Badung Market, Denpasar. As Bali’s largest traditional market, Badung Market is evolving into a digital-based cultural destination through the Smart Heritage Market concept. Employing a quantitative approach with a survey method, data were collected from 200 tourists who had visited the market and accessed its digital platforms. Using purposive sampling and a five-point Likert scale, the analysis reveals that: (1) website quality significantly influences tourist satisfaction; (2) memorable tourism experience positively affects both satisfaction and loyalty; (3) satisfaction significantly drives loyalty; (4) website quality indirectly influences loyalty through satisfaction as a mediating variable; and (5) loyalty also mediates the relationship between memorable experience and satisfaction. The findings highlight the strategic importance of enhancing website quality and creating memorable experiences to strengthen satisfaction and foster sustainable loyalty in digital cultural destinations.